2010
DOI: 10.1002/cne.22331
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of the serotonin 5‐HT1A receptor mRNA in chemically identified neurons of the mouse rostral brainstem: Implications for the role of serotonin in the regulation of wakefulness and REM sleep

Abstract: The 5-HT(1A) receptor (5-HT(1A)R) plays a key role in the inhibitory influence of serotonin (5-HT) on rapid eye movement (REM) sleep in rodents. However, the neuronal networks mediating such influence are mostly unknown, notably in the mouse. This led us to map 5-HT(1A)R mRNA, by in situ hybridization histochemistry (ISHH), and to characterize the neuronal phenotype of 5-HT(1A)R mRNA-positive neurons by dual ISHH and ISHH combined with immunohistochemistry, throughout the mouse rostral brainstem, a pivotal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 119 publications
(152 reference statements)
2
24
0
Order By: Relevance
“…In addition, it is possible that serotonin inhibition of cholinergic PPT occurs through other receptor subtypes or that selectivity for the 5-HT 1A receptor by 8-OH-DPAT is lost at high concentrations. Also, 5HT 1A serotonin receptor mRNA has only been found in GABAergic but not cholinergic neurons in the PPT of the mouse (38). Taken together, these data suggest that it is possible Grace et al (20) inhibited GABAergic or glutamatergic REM-on neurons to get an increase in REM sleep, whereas we selectively activated cholinergic REM-on neurons to get an increase in REM sleep.…”
Section: Implications For the Role Of Ppt And Ldt Cholinergic Neuronsmentioning
confidence: 52%
“…In addition, it is possible that serotonin inhibition of cholinergic PPT occurs through other receptor subtypes or that selectivity for the 5-HT 1A receptor by 8-OH-DPAT is lost at high concentrations. Also, 5HT 1A serotonin receptor mRNA has only been found in GABAergic but not cholinergic neurons in the PPT of the mouse (38). Taken together, these data suggest that it is possible Grace et al (20) inhibited GABAergic or glutamatergic REM-on neurons to get an increase in REM sleep, whereas we selectively activated cholinergic REM-on neurons to get an increase in REM sleep.…”
Section: Implications For the Role Of Ppt And Ldt Cholinergic Neuronsmentioning
confidence: 52%
“…Serotonergic regulation of NOS cells within this region could influence local circuit operations in response to stressor exposure. Prior investigations have demonstrated weak expression of the excitatory 5HT 2A receptor on cells of the LDT (Fay and Kubin, 2000), but beyond this study the 5HT receptor complement of this structure is not clear (Bonnavion et al, 2010). …”
Section: Introductionmentioning
confidence: 67%
“…Although 5-HT 1A receptor mRNA is present in the PPTn (Wright et al, 1995) it was not detected in rodent cholinergic PPTn neurons but was expressed by PPTn GABAergic neurons (Bonnavion et al, 2010). Although a previous study has shown that 5-HT inhibits cholinergic PPTn neurons in vitro (Leonard and Llinás, 1994), (Ϯ)8-OH-DPAT produced no effect in four of four cholinergic neurons tested whereas two neurons were hyperpolarized by (ϩ)8-OH-DPAT.…”
mentioning
confidence: 75%